2018
DOI: 10.1111/aogs.13474
|View full text |Cite
|
Sign up to set email alerts
|

Use of intrapartum ultrasound in term pregnant women with contractions before hospital admission

Abstract: Introduction The aim of this study was to test the hypothesis that transperineal ultrasound can be used to decide whether to admit a pregnant woman due to labor. Material and methods In this analytical cross‐sectional observational study, transperineal ultrasound was performed on pregnant women with intact membranes who came to the hospital due to contractions. A decision was made to admit women due to labor based on the ultrasound measurements. The ultrasound measurements were used to determine cervical dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…The characteristics of the included studies are shown in Table 1. Three of the studies were conducted in the UK [11,12,24], and seven in each of following countries: Spain [25], South Korea [7], Republic of Ghana [3], Tunisia [26], Sweden [27], Turkey [28], and Israel [15]. All studies were performed in the hospital setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included studies are shown in Table 1. Three of the studies were conducted in the UK [11,12,24], and seven in each of following countries: Spain [25], South Korea [7], Republic of Ghana [3], Tunisia [26], Sweden [27], Turkey [28], and Israel [15]. All studies were performed in the hospital setting.…”
Section: Resultsmentioning
confidence: 99%
“…Vaginal digital examinations were performed before or immediately after the ultrasound examination by the responsible birth attendant. Six studies recruited both nulliparous and multigravida women [3,7,15,24,25,28], and one study enrolled only nulliparous women [11]. One study used TLUS (trans-labial ultrasound) method, and other studies adopted TPUS (trans-perineal ultrasound) method.…”
Section: Resultsmentioning
confidence: 99%
“…This examination method can be painful, [6,7] associated with ascending infection [8] to the fetus and mother, and largely subjective. [9,10] Intrapartum ultrasound is better tolerated [11,12] by women than the traditional method of vaginal examinations and its use has been increasingly researched as an adjunct tool in labor for determination of cervical dilatation, fetal head position and station whilst maintaining sterility. Obstetricians can become competent in basic ultrasound techniques in order to recognize acute clinical emergencies as well as improve the recognition of labor arrest.…”
Section: Background and Rationale For Recommendationmentioning
confidence: 99%
“…Supplementing medical records with objective intrapartum ultrasound findings in the form of scan may help prove the validity of actions taken during labour (42) . It is hoped, though there is no evidence yet, that the use of intrapartum ultrasound will reduce the frequency of performing transvaginal digital examinations (34) , and hence contribute to lowering the risk of intrauterine infections.…”
Section: Applications Of Intrapartum Ultrasound In the Perinatal Periodmentioning
confidence: 99%
“…One study, performed on a small group of patients (57), showed that in the vast majority of cases (96.5%), a decision to admit pregnant women at term to hospital due to labour was possible based solely on the TPU findings which were consistent with the results of manual gynaecological examination. The authors ventured the conclusion that TPU performed before admitting a patient makes it possible to avoid up to 90% of transvaginal digital examinations (34) . The method could be particularly useful in cases of false labour, when the patient frequently undergoes a number of unnecessary transvaginal digital examinations.…”
Section: Applications Of Intrapartum Ultrasound In the Perinatal Periodmentioning
confidence: 99%